Perception of Family Health Strategy Workers on Oral Health Care Provided to Women and Children in the First 1,000 Days - Francenilde Silva de Sousa; Erika Barbara Abreu Fonseca Thomaz; Jullyanna Dias Cutrim; Isabelle Aguiar Prado; Ana Margarida Melo Nunes; Zeni Carvalho Lamy (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To analyze the perceptions of professionals from Primary Health Care Units (PHCU) concerning oral health care (OHC) provided during the first 1,000 days of life. Material and Methods: This qualitative study was conducted from August 2019 to July 2020. Collective interviews (focal groups) were conducted on health rights in the first 1,000 days in nine PHCUs in two contrasting municipalities in Maranhão. Seven collective interviews were conducted with 57 professionals from all PHCUs in municipality A and a health district in B. Content analysis was used in the thematic modality to perform data analysis. Results: Nine professionals spoke about oral health in the first 1,000 days. The statements were organized into two categories. In one of the categories, professionals mentioned barriers to accessing dental care due to myths about the possibility of treatment, which were not restricted to the users' knowledge but to that of the health professionals themselves. In the second category, the participants mentioned health education problems in which professionals are not heard and/or not understood by the community. Conclusion: There is a flaw in the training/continuing education of professionals concerning oral health in the first 1,000 days of life, especially regarding dental care during pregnancy. The participants still cannot help the population recognize dental care as a health right.